ERIL1, the plant homologue of ERI‐1, is involved in the processing of chloroplastic rRNAs. (5th October 2016) - Mermigka, Glykeria; Helm, Jutta Maria; Vlatakis, Ioannis; Schumacher, Heiko Tobias; Vamvaka, Evgenia; Kalantidis, Kriton
Summary: Proteins belonging to the enhancer of RNA interference‐1 subfamily of 3′–5′ exoribonucleases participate in divergent RNA pathways. They degrade small interfering RNAs (siRNAs), thus suppressing RNA interference, and are involved in the maturation of ribosomal RNAs and the degradation of histone messenger RNAs (mRNAs). Here, we report evidence for the role of the plant homologue of these proteins, which we termed ENHANCED RNA INTERFERENCE‐1‐LIKE‐1 (ERIL1), in chloroplast function. In vitro assays with At ERIL1 proved that the conserved 3′–5′ exonuclease activity is shared among all homologues studied. Confocal microscopy revealed that ERL1, a nucleus‐encoded protein, is targeted to the chloroplast. To gain insight into its role in plants, we used Nicotiana benthamiana and Arabidopsis thaliana plants that constitutively overexpress or suppress ERIL1. In the mutant lines of both species we observed malfunctions in photosynthetic ability. Molecular analysis showed that ERIL1 participates in the processing of chloroplastic ribosomal RNAs (rRNAs). Lastly, our results suggest that the missexpression of ERIL1 may have an indirect effect on the microRNA (miRNA) pathway. Altogether our data point to an additional piece of the puzzle in the complex RNA metabolism of chloroplasts. Significance Statement: In animals, Enhanced‐RNAi1 (ERI1) is an exoribonuclease regulator of RNAi and of rRNA maturation. Here we show that the plant homolog, ERIL‐1, is a chloroplast protein and that its misexpression affects chloroplast development, likely due to incorrect processing of chloroplast rRNA precursor molecules. In animals, Enhanced‐RNAi1 (ERI1) is an exoribonuclease regulator of RNAi and of rRNA maturation. Here we show that the plant homolog, ERIL‐1, is a chloroplast protein and that its misexpression affects chloroplast development, likely due to incorrect processing of chloroplast rRNA precursor molecules.